2006
DOI: 10.1111/j.0915-5635.2006.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Proper Selection of Colonoscope According to Gender, Age and Bmi of the Patient

Abstract: Background and Aim: Various types of colonoscope are available for total colonoscopy, including those with variable stiffness (VS) and/or magnetic endoscope imaging (MEI). Factors related to the patient, such as gender, age and body mass index (BMI), also affect the degree of technical difficulty associated with the procedure. The present study investigated, using retrospective analyses, which type of colonoscope was appropriate, in relation to gender, age and BMI, in order to overcome procedural difficulties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although reaching the cecum is essential to evaluate the entire colon, even experienced colonoscopists fail to reach the cecum with the colonoscope in approximately 2 % -10 % of cases [2,3]. Several studies have identified factors that influence the technical success of colonoscopy, revealing female sex, older age, lower body mass index (BMI), prior abdominal surgery, and patient pain as predictors of incomplete colonoscopy [4,5]. Various methods have been adopted to improve cecal intubation rates, including applying pressure to the abdomen, changing patient position, and using various devices and special scopes, such as the variable-stiffness colonoscope, gastroscope, pediatric colonoscope, and enteroscope.…”
mentioning
confidence: 99%
“…Although reaching the cecum is essential to evaluate the entire colon, even experienced colonoscopists fail to reach the cecum with the colonoscope in approximately 2 % -10 % of cases [2,3]. Several studies have identified factors that influence the technical success of colonoscopy, revealing female sex, older age, lower body mass index (BMI), prior abdominal surgery, and patient pain as predictors of incomplete colonoscopy [4,5]. Various methods have been adopted to improve cecal intubation rates, including applying pressure to the abdomen, changing patient position, and using various devices and special scopes, such as the variable-stiffness colonoscope, gastroscope, pediatric colonoscope, and enteroscope.…”
mentioning
confidence: 99%